ANALISIS PARAMETER OSEANOGRAFI DI PANTAI BINTALAHE AKIBAT LIMBAH BUANGAN BANGUNAN PEMBANGKIT LISTRIK TENAGA UAP (PLTU) - Latinulu, Atrila; Moh. Rizki Mooduto (Universitas Bina Taruna Gorontalo, 2025)
In the Bintalahe area, there is a coal-fired power plant (PLTU) that operates using steam power to generate electricity. This PLTU uses coal as fuel, which produces liquid waste from its operational processes. This study aims to analyze oceanographic parameters along the Bintalahe coastline due to the discharge of PLTU waste. The research was conducted from January 10–12, 2025, at Bintalahe Beach in Bone Bolango District using a descriptive method. The results of the study show that water quality parameters at Station 2 at a depth of 5 meters recorded a temperature of 31°C, while Stations 1, 2, and 3 at a depth of 3 meters had the same value of 30°C. The highest dissolved oxygen (DO) measurement was at station 1 at 7.1 mg/L, station 2 at a depth of 3 meters at 6.4 mg/L, at a depth of 5 meters at 6.9 mg/L, and the lowest at station 3 at 4.1 mg/L. Salinity measurements showed Station 1 at 30‰, Station 2 at 3 meters depth at 25‰, at 5 meters depth at 27‰, and Station 3 at 25‰. Light intensity reached 100% at all observation stations. Current speed varied with Station I at 0.56 m/s, Station II at 3 meters depth at 1.12 m/s, 5 meters depth at 1.19 m/s, and Station III at 1.47 m/s.